A Hybrid Assessment Model For Barriers Hindering The Adoption Of Sustainable Interior Design Practice In Malaysia - Ashour, Mojtaba (2021)
While the notion of sustainability has long been a major concern in the built environment, the practice of sustainable interior design (SID) still falls short. This research aimed to investigate the deficiency in the practice of SID in Malaysia. To this end, after identifying 30 potential barriers through a review of literature, a two-round Enhanced Fuzzy Delphi Method (EFDM) involving 13 qualified Malaysian experts was employed resulting in the exclusion of 10 barriers and the addition of one new barrier. To prioritize the barriers, a novel hybrid method, the Parsimonious Cybernetic Fuzzy Analytic Hierarchy Process (P-CFAHP) was introduced, significantly reducing the number of pairwise comparisons, and eliminating the need for a complicated AHP questionnaire. Results showed the highest prioritized barriers are: (1) lack of sufficient sustainability modules in the education of interior designers, (2) designers’ lack of experience and technical understanding, (3) lack of codes, regulations, and specific legal frameworks designed for different types of projects, (4) lack of interest from the client, and (5) designers’ lack of training. Semi-structured interviews were conducted with experts and potential solutions concerning education, regulations, standards, and policies are provided on how to overcome these barriers. The findings of this research provide valuable insights for professional interior designers, educators, statutory authorities, governments, and policymakers. Considering the dearth of literature, this research fills the existing gap and establishes the groundwork by identifying the issues faced by interior designers in developing countries, and introduces a novel P-CFAHP that has not been employed before.